Whey protein enriched with Stevia rebaudiana fraction restores the pancreatic function of streptozotocin induced diabetic rats - Milani, Paula Gimenez (2020)
The study aims to analyse the treatment of whey protein enriched withStevia rebaudianafraction in insulin secretion and its role mitigating streptozotocin-induced hyperglycemia in rats. Thus, diabetic animals were treated with whey protein enriched withS. rebaudianafraction or with only the protein isolate or only the Stevia fraction. Insulin level in plasma was measured by radioimmunoassay and the viability of beta cells was detected by immunohistochemistry. The results showed that diabetic animals treated with whey protein enriched withS. rebaudianafraction had a greater recovery from insulinemia, with plasma levels similar to non-diabetic animals (similar to 0.13 ng/mL). In addition, the same group showed a higher number of insulin-positive pancreatic B cells (similar to 66%) in immunohistochemistry analysis, while the diabetic groups treated with only the fraction of stevia or whey protein showed 38 and 59% of positive cells, respectively. These results show that the treatment may have restored the viability of streptozotocin-injured pancreatic B cells, and consequently increased insulin secretion, suggesting whey protein enriched withS. rebaudianafraction can be used an adjunct/supplement in diabetic treatment.